The protective role of competitive sports in reducing suicidality amongst youth athletes - Sparagana, Paola R.; Clark, V. Claire; Herge, Whitney; Stapleton, Emily J. (Frontiers in Psychology, 2025)
IntroductionSuicidality is a critical concern among young people, and a prevalent concern in athletes. This study aimed to investigate the rate of suicidality among youth athletes in sports medicine clinics and to evaluate the risk for suicidality in this population.MethodsA retrospective chart review of 8,599 patients (10–18 years old) seen between 2018 and 2022 was conducted using the Ask Suicide-Screening Questionnaire (ASQ). Analyses examined relationships between ASQ responses and demographic, clinical, and sport-related variables.ResultsAmongst athletes, higher competition levels were associated with lower rates of suicidality than those competing at lower levels (p = 0.0162). While female sex was associated with increased suicidality overall, this was not significant within the athlete subgroup.DiscussionHigher levels of sport competition were associated with lower rates of suicidal ideation, suggesting a potential protective effect.